An ionicity rationale to design solid phase metal nitride reactants for solar ammonia production - Michalsky, Ronald; Pfromm, Peter H. (My University, 2012)
Ammonia is an important fertilizer component and could be used as a convenient hydrogen carrier. This work studies a solar thermochemical reaction cycle that separates the reductive N[subscript 2] cleavage from the hydrogenation of nitrogen ions to NH[subscript 3] without using electricity or fossil fuel. The hydrolysis of binary metal nitrides of magnesium, aluminum, calcium, chromium, manganese, zinc, or molybdenum at 0.1 MPa and 200-1000°C recovered up to 100 mol% of the lattice nitrogen with up to 69.9 mol% as NH[subscript 3] liberated at rates of up to 1.45 x 10ˉ³ mol NH[subscript 3] (mol metal)ˉ¹ sˉ¹ for ionic nitrides. These rates and recoveries are encouraging when extrapolated to a full scale process. However, nitrides with lower ionicity are attractive due to simplified reduction conditions to recycle the oxidized reactant after NH[subscript 3] formation. For these materials diffusion in the solid limits the rate of NH3 liberation. The nitride ionicity (9.96-68.83% relative to an ideal ionic solid) was found to correlate with the diffusion constants (6.56 x 10[superscript -14] to 4.05 x 10[superscript -7] cm² sˉ¹) suggesting that the reduction of H[subscript 2]O over nitrides yielding NH[subscript 3] is governed by the activity of the lattice nitrogen or ion vacancies, respectively. The ionicity appears to be a useful rationale when developing an atomic-scale understanding of the solid-state reaction mechanism and when designing prospectively optimized ternary nitrides for producing NH[subscript 3] more sustainably and at mild conditions compared to the Haber Bosch process.
Keywords: Solar radiation; Heterogeneous catalysis; Transition metal nitride; Transition metal oxide; Nitrogen diffusion; Mulliken population analysis